Produktivitas dan Efisiensi Teknis Usahatani Padi Organik Lahan Sawah - Adi Prayoga (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
EnglishResearch on productivity and technical efficiency of lowland organic rice was conducted in Sukorejo and Jambeyan villages, Sambirejo District, Sragen Regency. The research applies interview techniques to obtain primary data from 120 respondents. The respondents are selected using non proportionate stratified random sampling technique which is divided into equal size of four levels. This research aims to analyze the productivity, technical efficiency and source of technical inefficiency of organic rice, and compare the results with conventional rice performance. Productivity is measured by total factor productivity approach applies TFP index value. Technical efficiency is measured by using frontier production function and is estimated using MLE method assuming that Cobb-Douglas is the functional form of farm organic rice in the research areas. Estimation source of technical inefficiency applies linear regression model that approach simultaneously using frontier production function. The research result indicates that organic rice farmer’s performance of the eighth year and the fifth year is more productive than the conventional rice farmers. The level of technical efficiency varies from 0.47 to 0.96 with the average of 0.70. The level of technical efficiency of organic rice farmers of the eighth year and the fifth year is higher significantly compared to the conventional rice farmers. The result also shows that the number of productive age of family members and the frequency to attend extension activities is influencing to reduce technical inefficiency.IndonesianPenelitian produktivitas dan efisiensi teknis usahatani padi organik lahan sawah dilakukan di Desa Sukorejo dan Jambeyan, Kecamatan Sambirejo, Kabupaten Sragen menggunakan responden sebanyak 120 orang yang dipilih dengan teknik non proportionate stratified random sampling yang terbagi sama besar dalam empat strata. Penelitian ini bertujuan untuk menganalisis produktivitas, efisiensi teknis dan sumber inefisiensi teknis padi organik, serta membandingkan dengan padi konvensional. Produktivitas diukur dengan pendekatan produktivitas faktor total menggunakan angka indeks TFP. Efisiensi teknis diukur dengan menggunakan fungsi produksi frontier yang diestimasi dengan metode MLE, dengan mengasumsikan Cobb-Douglas adalah bentuk fungsional usahatani padi organik di daerah penelitian. Estimasi sumber inefisiensi teknis menggunakan model regresi linier yang diestimasi secara simultan dengan fungsi produksi frontier. Hasil Penelitian menunjukkan bahwa petani padi organik tahun ke-8 dan tahun ke-5 lebih produktif dibandingkan petani padi konvensional. Tingkat efisiensi teknis yang dicapai petani sampel bervariasi antara 0,47 – 0,96 dengan rata-rata 0,70. Tingkat efisiensi teknis petani padi organik tahun ke-8 dan tahun ke-5 lebih tinggi secara signifikan dibandingkan petani padi konvensional. Hasil penelitian juga menemukan bahwa jumlah anggota keluarga usia produktif dan frekuensi mengikuti kegiatan penyuluhan berpengaruh menurunkan inefisiensi teknis.